Fundamentals of Academic Writing: A Literature Review - Chauhan, Padam (Journal of NELTA, 2022)
In order to write for academic purposes, all novice ESL and EFL writers must be well-informed about the fundamentals of academic writing (AW) in English. Developing academic writing skills for all students is crucial because they must produce good writing skills to meet the standards of college and university course writing assignments. The typical college and university writing assignments include descriptive writing, analytical writing, persuasive writing, critical writing, and inquiry writing. In the meantime, it is also crucial for them to understand that writing is a recursive process involving various stages, such as generating ideas, outlining, planning, drafting, revising, editing, and sharing. During the writing process, the writers should not only consider the elements of AW, comprising content, organization, purpose and audience, critical thinking, word choice, grammar, and mechanics, but also its basic conventions, including objectivity, formality or style, citation style, simplicity, clarity and conciseness, and genre awareness. Against this background, the primary purpose of this paper is to review the fundamentals of academic writing. The paper ﬁ rst deﬁnes AW as an art, science, and craft. It then brieﬂy discusses the main types of writing students must produce as a part of their college and university course assignments. Finally, the paper highlights some key features of research-based writing tasks generally assigned to graduate students, such as reading responses or reaction papers, reﬂection papers, research papers, and theses and dissertations.